The German Musical Exile and the Course of American Musicology - Josephson, David (Current Musicology, 2005)
On the face of it, the subject would seem not to need a paper. Musicology was a European discipline fed from many sources, named by Friedrich Chrysander (1863, 1867), defined by Guido Adler (1885), and, during its early twentieth-century course, shaped by Friedrich Ludwig and Hugo Riemann. Like other humanities during the muscular growth of Wilhelmine Germany, it became a German province. As America had taken its classical music from Germany during the nineteenth century, so it took its musicology from Germany in the early years of the twentieth. But our pioneers soon set out to create a distinctly American musicology, and were on their way to doing so from the founding of the Musical Quarterly in 1915 to the creation of the New York Musicological Society in 1931 and its reorganization as the American Musicological Society (AMS) three years later.3 They were soon overtaken by an unexpected influx of emigre scholars in flight from central Europe whose numbers and prestige charted the course of the fledgling discipline anew. Eventually, as the emigres passed from the scene, and the generations of those they had taught began to pass from it as well, their influence eroded and American musicology reclaimed its national character, however that character would come to be construed. It seems a straightforward story. It isn’t. That story tells us little about why we did what we did during the early decades of our Society’s existence. It narrates the meteoric rise of the emigres’ influence, but fails to account for its seemingly sudden collapse. When in 1985 Joseph Kerman published a stunning critique of postwar Anglo-American scholarship-he had been fighting the battle for twenty years before that-Margaret Bent responded as President of the AMS with an Address at the Society’s annual meeting that year in Vancouver, defending the classic paradigm with the authority of one who was its elegant voice and the passion of one who recognized what was at stake (Kerman 1985; Bent 1986). But by the annual meeting in 1990 in Oakland the field had become a Babel of voices.